Experimental study on thermal conductivity and microscopic characterization of sandy clay in deep buried formation - Yi Cao; Yansen Wang; Chuanxin Rong; Hao Li; Bin Wang; Xin Shi; Jie Zhang (Soils and Foundations)
The thermal conductivity of soil is a key factor influencing the heat transfer process and temperature distribution, which has significant implications for the design and implementation of freezing methods in geotechnical engineering. To address the challenge of freezing the deeply buried sandy clay layer using the freezing method in the drilling wells of the Huainan-Huaibei mining area, experimental research was conducted on the thermal conductivity of sandy clay and its microstructure. Utilizing the transient plane source method, variations in thermal conductivity with water content, dry density, sand content, and temperature were observed, revealing the patterns and mechanisms underlying these changes. The findings indicate that the thermal conductivity of frozen sandy clay mainly undergoes three stages of temperature variation. During the rapid increase phase (Ⅱ), the thermal conductivity rises sharply with decreasing temperature, exhibiting a “leap” trend. As the water content increases, the range of the thermal conductivity leap gradually narrows. When the water content increases from 15 % to 22.5 %, the corresponding leap range decreases to 0 ∼ -5℃. Microstructural parameters quantitatively reflect the intrinsic reasons for changes in soil thermal conductivity from a microscopic perspective, indicating that these characteristics significantly affect its thermal conductivity.